Integrative mindfulness-based infant parenting program: theoretical foundations and a novel intervention protocol - Burstein, Or; Teshale Zevin, Zipi; Geva, Ronny (Frontiers in Psychology, 2025)
Infancy is a formative period in which high-quality parental care plays a vital role in setting solid foundations that guide a child’s development. Mindfulness has been recognized for enhancing parental awareness and sensitivity to both self and child and can be utilized in clinical practice to facilitate healthy development. To adapt mindful parenting practice for implementation in pediatric care settings and the specific needs and challenges of parenting infants, the current study introduces a novel theoretical framework, combining mindfulness with elements from calming cycle theory, dialectical behavior therapy (DBT), trauma-informed care, emotion-focused therapy, schema therapy, and Vygotsky’s learning theory. These elements are not merely complementary but cardinal in meeting the diverse needs of parents during infancy, both in typical developmental contexts and following preterm birth, where additional stressors are often present. The study delineates the theoretical foundations of this integrative mindfulness-based approach and openly provides a novel comprehensive protocol of an 8-week group intervention program that operationalizes the proposed framework. This program focuses on enhancing parental mindful observation, non-judgmental acceptance, and goal-driven behavior to strengthen the resilience of the parent-infant relationship. Emphasizing the bi-directional nature of this relationship and the role of co-regulation with the child, the theory-derived program is designed to scaffold calming dyadic cycles, promote reconsolidation of birth-related adverse experiences, and facilitate flexibility in parental modes. The novelty of this intervention lies in its holistic approach to mindful parenting, conjoining diverse theoretical perspectives into a coherent, culturally adaptable, and clinically oriented protocol that can be assimilated in pediatric community clinics. The provided protocol may now enable the evaluation of the framework’s effectiveness in attaining positive effects for parents and children.